QUALITY OF LIFE OF USERS OF LONG-TERM HEALTH CARE - Zlatanović, Milena; Osmanspahić, Adnan; Despotović, Mile; Hadživuković, Natalija; Pavlović, Jelena; Matović, Sandra; Živanović, Srđan; Zlatanović, Milena; Despotović, Milena; Kucurski, Ljubiša (PONS - medicinski časopis, 2024)
Introduction. Long-term care represents a series of health and social care services that are provided at home or in an institutional environment to people with reduced functional capacity (reduced physical and/or cognitive abilities) who need support in performing daily activities, and who depend on the help of others for a long time period. The goal of the research was to examine the quality of life of users with long-term health care, with a special focus on comparing the quality of life between people placed institutionally and outside of the institution. Methods. The research was designed according to the principle of a cross-sectional study. In the research, a general questionnaire and a scale for assessing the quality of life Short Form 36 Health Survey (SF-36) were used. Among the statistical tests, the χ2 square test was used. The usual value of p<0.05 was taken as the level of statistical significance. Results. Subjects who were institutionalized had statistically significantly lower values of domains and summary scores of quality of life compared to subjects whose health care took place outside of institutions, whereby the difference was observed in physical functioning (p<0.001), social functioning (p=0.003 ) and mental health summary score (p=0.015). Conclusion. Users of long-term health care placed in an institution had significantly worse physical functioning, a higher level of limitations due to physical problems, worse general health, a lower level of social functioning, as well as mental health. Key words. long-term health care, quality of life, institutional users, non-institutional users.